2008
DOI: 10.1016/j.vaccine.2008.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of immunostimulatory properties of exosomal vaccines by incorporation of fusion-competent G protein of vesicular stomatitis virus

Abstract: Exosomes have been proposed as candidates for therapeutic immunization. The present study demonstrates that incorporation of the G protein of vesicular stomatitis virus (VSV-G) into exosome-like vesicles (ELVs) enhances their uptake and induces the maturation of dendritic cells. Targeting of VSV-G and ovalbumin as a model antigen to the same ELVs increased the cross-presentation of ovalbumin via an endosomal acidification mechanism. Immunization of mice with VSV-G and ovalbumin containing ELVs led to an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 32 publications
0
60
0
Order By: Relevance
“…For a conventional Ova-expressing adenoviral vector, we used the previously described vector Ad-⌬GM-OVA (40), which shall be referred to as Ad5.ova in this publication. Ova-coated exosomes (Exo-ova) were produced as described previously (39). The Ova amounts on Ad5.pIX-ova and Exo-ova were determined by enzyme-linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a conventional Ova-expressing adenoviral vector, we used the previously described vector Ad-⌬GM-OVA (40), which shall be referred to as Ad5.ova in this publication. Ova-coated exosomes (Exo-ova) were produced as described previously (39). The Ova amounts on Ad5.pIX-ova and Exo-ova were determined by enzyme-linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were immunized once with an adenoviral Ova expression/display vector, a conventional Ova-expressing adenoviral vector, or with Exo-ova. The exosomes display Ova that is anchored to the exosome membrane by fusion to the transmembrane domain of the G protein of vesicular stomatitis virus (39). Exo-ova served as an antigen display-only control.…”
Section: The Cd4mentioning
confidence: 99%
“…Temchura et al decorated antigen-loaded EVs with a vesicular stomatitis virus G (VSV-G) protein to stimulate the cross-presentation of these antigens in recipient DCs [142]. The VSV-G protein promotes the fusion of lipid membranes at lower pH (i.e.…”
Section: Intracellular Trafficking Of Evsmentioning
confidence: 99%
“…~6) and can thus drive destabilization of the endosomal/phagosomal membrane following internalization [143]. These authors showed that the VSV-G protein stimulated MHC I mediated antigen presentation and elicited an antigen-specific CD8 + T cell response [142]. The previously mentioned RVG targeting ligand [119,144,145] and iRGD [133,146] have also been reported to have membrane-destabilizing properties, possibly contributing to enhanced cytoplasmic delivery of the encapsulated cargo.…”
Section: Intracellular Trafficking Of Evsmentioning
confidence: 99%
“…40 Interestingly, induction of apoptosis in cancer cells via notch signaling 41 and PI3K/Akt/GSK-3β survival pathways 42 is observed when TEX interacts with pancreatic cancer cells. Apart from stimulating the adaptive immune system by cross-priming cytotoxic T cells, 43 it has also been demonstrated that TEX can activate the innate immune system by increasing IgG antibody response 44 and NK cells. 45 When dendritic cells are pulsed with cancer antigens or tumor peptides, 46 DEX has been shown to elicit stronger immune responses toward cancer cells, 47 with upregulation of specific antibody release and cytokine production.…”
Section: A Nanoscale and Cell-free Cancer Vaccinementioning
confidence: 99%